The Capability Approach as a Normative Framework for Urban Biodiversity Management: Strong Points and Unresolved Issues - Melin, Anders (De Ethica, 2026)
The Capability Approach (CA) has since the 1990s become one of the most influential theories of justice. It has been proven to be helpful for analysing both questions of social, environmental and multispecies justice. This article contributes to the debate on the usefulness of the CA in the context of ecological sustainability by evaluating its appropriateness as a normative framework for urban biodiversity management. The paper concludes that in its present form, it is uncertain whether the CA is suitable as a normative framework in this context. Its multidimensional view of human welfare can be considered a strong point, but there are also important unresolved issues. There are reasons for considering a redefinition of the concept of capability as it is problematic to apply to animals and even more so to plants. Finally, the question of whether collective entities should be considered for their own sake within the CA challenges the ethical individualism that is a core assumption in most formulations of the CA.